New bacterial growth in bronchial secretions after bronchoscopic valve implantation - Sarmand, Nilab; Gompelmann, Daniela; Kontogianni, Konstantina; Polke, Markus; Herth, Felix; Eberhardt, Ralf (The International journal of chronic obstructive pulmonary disease, 2018)
New bacterial growth in bronchial secretions after bronchoscopic valve implantation Nilab Sarmand,1 Daniela Gompelmann,1,2 Konstantina Kontogianni,1 Markus Polke,1 Felix JF Herth,1,2 Ralf Eberhardt1,2 1Department of Pulmonology and Respiratory Care Medicine, Thoraxklinik, at the University of Heidelberg, Heidelberg, ²Translational Lung Research Center Heidelberg, Member of the German Center for Lung Research DZL, at the University of Heidelberg, Heidelberg, Germany Background: Bronchoscopic valve implantation is an established treatment in selected patients with severe lung emphysema. There is evidence in literature of increased bacterial colonization of various implants. So far, it is unclear if an increased bacterial colonization can also be observed after endoscopic valve therapy. Methods: Retrospective analysis of patients with examination of the bronchial secretions for presence or change of bacterial growth before and after valve implantation. Results: Overall, 144 patients who underwent bronchoscopic follow-up after valve implantation were included in this analysis. Prior to valve placement, only 7 out of 144 consecutive emphysema patients (5%) presented with evidence of bacterial colonization, whereas 137 patients (95%) showed no bacterial growth prior to valve placement. One hundred seven out of the 137 patients (78%) showed new bacterial growth after valve implantation. Almost 38% of the patients who presented with a new bacterial growth had evidence of Viridans streptococci, Rothia mucilaginousa and Neisseria species simultaneously, as bacterial colonization. Pathogenic bacterial growth was recorded for Staphylococcus aureus (18%), Pseudomonas aeruginosa (13%) and Stenotrophomonas maltophilia (9%) microorganisms. There was also a significant bacterial growth by Moraxella catarrhalis (26%) and anaerobic bacteria (23%), especially in patients with complete atelectasis after successful endoscopic lung volume reduction. For all of the 7 patients, the presented initial bacterial colonization showed a change in the flora after bronchoscopy valve implantation. Conclusion: In this study we observed an increased bacterial colonization in the long term after valve implantation. This finding needs further evaluation regarding its possible clinical relevance but should be taken into consideration in the follow-up of these patients. Keywords: valve implantation, lung volume reduction, bacterial growth, COPD
Gesehen am 21.05.2019